Content Validity of Self-Talk Guidance as a Psychological Skill Training Tool for Athletes - Adiska Rani Ditya Candra; S Sobihin; Dewangga Yudhistira; Wiga Nurlatifa Romadhoni; Anggit Wicaksono; Gustiana Mega Anggita; Mohammad Arif Ali (Universitas Pendidikan Indonesia, 2023)
Psychological factors that can potentially improve athlete performance are called Psychological Skills Training (PST). PST refers to psychological skill training that is systematic and consistent in improving the athlete’s performance and achievement. Studies on the effectiveness of psychological techniques, such as self-talk, imagery, and goal setting, are often used as training tools for athletes. This study aimed to determine the content validity of the Self-talk Guide Book developed as a guide for implementing psychological exercises for athletes. This Book contained the types of self-talk, how to apply it, and ways for athletes to easily respond to any negative self-talk arising in their minds. The research used Research and Development method with the ADDIE design which focused on the